Nonmotor Symptoms in Parkinson’s Disease in 2012: Relevant Clinical Aspects - Anne Marie Bonnet; Marie France Jutras; Virginie Czernecki; Jean Christophe Corvol; Marie Vidailhet (Parkinson's Disease)
Nonmotor symptoms (NMSs) of Parkinson’s disease (PD) are common, but they are often underrecognized in clinical practice, because of the lack of spontaneous complaints by the patients, and partly because of the absence of systematic questioning by the consulting physician. However, valid specific instruments for identification and assessment of these symptoms are available in 2012. The administration of the self-completed screening tool, NMSQuest, associated with questioning during the consultation, improves the diagnosis of NMSs. NMSs play a large role in degradation of quality of life. More relevant NMSs are described in this review, mood disorders, impulse control disorders, cognitive deficits, hallucinations, pain, sleep disorders, and dysautonomia.